Successful treatment of breast cancer‐related breast lymphedema by lymphovenous anastomosis in a male patient. Issue 4 (19th March 2019) - Giacalone, Guido; Yamamoto, Takumi; Belva, Florence; Wets, Rudiger; Hayashi, Akitatsu; Koshima, Isao
Abstract : Men, as well as women may develop breast lymphedema following breast cancer treatment. Microsurgically performed lymphovenous anastomosis (LVA), an effective treatment for lymphedema of the extremities, has also been successfully applied to breast lymphedema. Here we report the first case of breast lymphedema secondary to male breast cancer, treated with supermicrosurgical LVA. A 48‐year‐old man presented with breast lymphedema following mastectomy, axillary lymph node dissection, and adjuvant radiotherapy. After the oncological treatments, the patient reported a sensation of tension, pain, and swelling of the left breast. The diagnosis of breast lymphedema was confirmed by lymphoscintigraphy. Since conservative treatment with manual lymphdrainage was ineffective, we performed LVAs at the left breast region. In total, two lymph vessels were anastomosed to two nearby veins. Immediately following this intervention, the left breast and lateral thorax region decreased in size and the sensation of tension disappeared. One year postoperative there was no recurrence of the swelling and the patient was very satisfied with the result. Although more reports are needed to confirm its efficacy, supermicrosurgical LVA appears to be a valuable treatment option for breast lymphedema in both women and men.